The Infectiousness of Crowds: Crowding Experiences Are Amplified by Pathogen Threats. (January 2019) - Wang, Iris M.; Ackerman, Joshua M.
People sometimes perceive social environments as unpleasantly crowded. Previous work has linked these experiences to incidental factors such as being hungry or hot and to the relevance of the social environment for an individual's current goals. Here, we demonstrate that crowding perceptions and evaluations also depend on specific, active threats for perceivers. Eight studies test whether infectious disease threats, which are associated with crowded conditions, increase such reactions. Across studies, pathogen threat made dense social environments seem more crowded and generated more negative affect toward these environments. These perceptions and negative feelings were more influenced by pathogen threat relative to other threats of physical danger. Finally, reactions to pathogen threat affected people's choice of crowded versus uncrowded environments to inhabit. This research suggests that interpretations of social environments depend on the unique threats and opportunities those environments afford to individuals.